Design of plasma needle and high frequency power supply for bio medical applications [electronic resources] - Lee, Chengxu, 1988-, author (2012)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2012